“The Effect of Indonesia Tax Amnesty 2016 law Validation towards Indonesia Stock Exchange (Event Study on Companies Classified in LQ45 Index)” - I.W. Budhisastrawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is an event study which aimed at finding out empirical evidence related to whether or not the Tax Amnesty 2016 Law Validation affects Indonesia’s capital market. The population in this research was 45 listed companies in Indonesia Stock Exchange’s stocks classified in LQ45 index. This research used secondary data which were daily stock price, daily trading volume, and the composite index on five days before, one day at the event date, and five days after the event date. Statistical test in this research used one-tailed t-test and paired t-test. There is significant positive abnormal return around the event date which means that the market responds towards the event. There is no significant difference in abnormal return on the pre-event to event date, event date to post-event, and pre-event to post-event period. There is significant difference on the pre-event to event date and event date to post-event period, but not significant on the pre-event to post-event period.Keywords:Event Study, Capital Market, Abnormal Return, Trading Volume Activity